'Fighting Stick of Thunder': Firearms and the Zulu Kingdom: The Cultural Ambiguities of Transferring Weapons Technology. (October 2014) - Laband, John
Abstract : This paper investigates the reluctance of the nineteenth-century Zulu people of southern Africa fully to embrace firearms in their war-making, and posits that this was an expression of their military culture. Not that the Zulu could not appreciate the battle-winning potential of the new military technology, or were dissuaded from increasingly determined efforts to obtain large quantities of firearms from traders. Yet, because firearms were prestigious weapons, monopolized by the elite, or professional hunters, Zulu commoners had little opportunity to master them and continued to rely instead on their traditional weapons, particularly the stabbing-spear. Even so, cultural rather than practical reasons were behind the rank and file's reluctance to upgrade firearms to their prime weapon. Employing recorded contemporary Zulu oral evidence, praise songs, and statements of prisoners-of-war, to unpack the Zulus' own perception of their heroic military culture, it is argued that, because of the engrained Zulu cultural consensus that only hand-to-hand combat was appropriate conduct for a true fighting-man, killing at a distance with a firearm was of inferior significance, and did not even entail the ritual pollution that followed homicide and the shedding of human blood. Only close combat was worthy of praise and commemoration.